AIP Conference Proceedings 2008
DOI: 10.1063/1.3076516
|View full text |Cite
|
Sign up to set email alerts
|

Switching Criteria for Hybrid Rarefied Gas Flow Solvers

Abstract: Switching criteria for hybrid hydrodynamic/molecular gas flow solvers are developed, and are demonstrated to be more appropriate than conventional criteria for identifying thermodynamic non-equilibrium. For switching from a molecular/kinetic solver to a hydrodynamic (continuum-fluid) solver, the criterion is based on the difference between the hydrodynamic non-equilibrium fluxes (i.e. the Navier-Stokes stress and Fourier heat flux) and the actual values of stress and heat flux as computed from the molecular so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…For each of the species, the density has been set such that the body-length Knudsen number Kn BL is 0.05. Studies on different breakdown parameters for similar test cases [36,37] show that the non-equilibrium originates from the Knudsen layer near the wall. For this reason, the CFD and DSMC domains are consider appropriate for the complete simulation, and will not be updated.…”
Section: Resultsmentioning
confidence: 97%
“…For each of the species, the density has been set such that the body-length Knudsen number Kn BL is 0.05. Studies on different breakdown parameters for similar test cases [36,37] show that the non-equilibrium originates from the Knudsen layer near the wall. For this reason, the CFD and DSMC domains are consider appropriate for the complete simulation, and will not be updated.…”
Section: Resultsmentioning
confidence: 97%
“…Alternatively, some researchers have developed other formulations of continuum breakdown parameters by measuring the departure from hydrodynamic behavior. For example, Lockerby et al [19] proposed a new criterion based on the difference between the hydrodynamic near-equilibrium fluxes (the Navier-Stokes stress and Fourier heat flux) and the actual values of stress and heat flux (computed from molecular simulations or approximated through higher order constitutive relations); Meng et al [20] proposed a kinetic criterion based on the molecular distribution function to indirectly assess the errors introduced by the description using NSF equations. Their numerical tests demonstrated that the new criterion performs very well in both low-speed and high-speed flows.…”
Section: Continuum Breakdown Criterionmentioning
confidence: 99%
“…For problems such as this, where the degree of scale separation varies as the system evolves, we define a local scale-separation number (analogous to the local Knudsen number for rarefied gas flows, e.g., [7,8]) that compares the shortest relaxation time scale of the system (T micro ) with a time scale that characterises the evolution of the coupling variables:…”
Section: Example I: Step Response Of Coupled Odesmentioning
confidence: 99%